Study of Fisheries Law For The Development of the Aquaculture Sector In Land Based Areas - Ahmad Hasyim Asari Taufiqurrohman; Dwi Edi Wibowo; Heri Ariadi (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Aquaculture sector is an important fishery agribusiness activity. The purpose of this research is to find out the problems in the application of fisheries law in the aquaculture sector in land based areas as well as efforts to develop strategies. The research method used is normative legal method by taking respondent samples by deep interviews and questionnaire distributions. Aquaculture activities in land based areas are a profitable agribusiness development option. Aquaculture activities problem in land based areas include socio-cultural, economic, and resource management issues. Based on the existing problems and potential maps several options for resolution strategies are generated, such as: establishing special conservation regulations, education of UU No. 31/2004 and its implementation, developing agribusiness businesses, making standard management procedures, product innovations, and forming active communities. Implementation of the strategy will be developed in 2 aspects this non-legal aspects (public education, making regulations, community participation) and legal aspects (preventive and repressive actions). The conclusion of this study is that the main problem of the weak fisheries law application on aquaculture sector in land based areas is that aquaculturist still lack knowledge about the fisheries legal context, then to overcome this problem an implementative strategy is needed from the study of legal aspects and non-legal.